STRATEGI PEMBELAJARAN GURU DI MASA PANDEMI COVID-19 DI SMP NEGERI 3 FAOMASI LAHOMI KABUPATEN NIAS BARAT - Baharui Daeli (Universitas Nias Raya, 2023)
Due to the COVID-19 pandemic, the learning process has changed, which was originally done face-to-face, and was replaced by distance learning (online). However, in the implementation of online learning, there are several obstacles from an unstable network, inadequate internet quota, and students not having an android phone. Teachers need to design learning strategies in overcoming these problems. The aims of this study were: 1) To find out the process of implementing teacher learning strategies during the covid-19 pandemic. 2) To find out the student learning process during the covid-19 pandemic. This type of research is qualitative research through a descriptive approach. Data collection techniques are interviews, observations, and documentation studies. Research results: Teacher learning strategies during the covid-19 pandemic are online learning strategies, online learning strategies, and study group learning strategies. The student learning process during the COVID-19 pandemic is going well. Research conclusions: The learning strategies used by teachers are effective during the covid-19 pandemic as alternative learning during the covid-19 pandemic, students are more independent, emphasize more on student centeredness, students are more daring to express their opinions and ideas, students are more creative in doing their work. tasks such as being able to make videos that previously lacked understanding in making videos, adding insight and student learning experiences through unlimited learning resources such as from youtube and the internet. The researcher's suggestions are: For schools, they should facilitate teachers more in the implementation of learning, especially in the implementation of learning during the covid-19 pandemic. For teachers, they should further develop learning and improve teacher competence regarding the use of ICT, so that the readiness of learning activities using technology as it is today can be maximized.